Dimenticare Napoleone? Storia, letteratura, arti intorno alla figura dell'imperatore francese - Pilo, Rafaella (Quaderni del Corso di laurea in Filosofia, 2023)
The seminar held in December 2021, of which this volume is an outcome, made it possible to place the figure of the Emperor of the French in a multidisciplinary research context and to carry out a cultural policy action aimed at not forgetting historical events, with a response approach to controversies related to the political correct approach and the spread of cancel culture.